2015
DOI: 10.3390/md13127073
|View full text |Cite
|
Sign up to set email alerts
|

Distribution in Different Organisms of Amino Acid Oxidases with FAD or a Quinone As Cofactor and Their Role as Antimicrobial Proteins in Marine Bacteria

Abstract: Amino acid oxidases (AAOs) catalyze the oxidative deamination of amino acids releasing ammonium and hydrogen peroxide. Several kinds of these enzymes have been reported. Depending on the amino acid isomer used as a substrate, it is possible to differentiate between l-amino acid oxidases and d-amino acid oxidases. Both use FAD as cofactor and oxidize the amino acid in the alpha position releasing the corresponding keto acid. Recently, a novel class of AAOs has been described that does not contain FAD as cofacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 122 publications
1
27
0
Order By: Relevance
“…Like other members of the L-amino acid oxidases (EC 1.4.3.2. ), LysOx from T. viridae is a flavoprotein with noncovalently bound FAD and catalyzes the stereospecific oxidative deamination of an L-amino acid, thereby producing ammonia and hydrogen peroxide as by-products (Lukasheva and Berezov, 2002;Pollegioni et al, 2013;Campillo-Brocal et al, 2015). The formal product of the oxygen-consuming and hydrogen peroxide-generating oxidation of the a-carbon atom of L-Lys is KAC, which is described to further cyclize to 1,2-DP if the reaction is conducted in the presence of catalase (Kusakabe et al, 1980;Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Like other members of the L-amino acid oxidases (EC 1.4.3.2. ), LysOx from T. viridae is a flavoprotein with noncovalently bound FAD and catalyzes the stereospecific oxidative deamination of an L-amino acid, thereby producing ammonia and hydrogen peroxide as by-products (Lukasheva and Berezov, 2002;Pollegioni et al, 2013;Campillo-Brocal et al, 2015). The formal product of the oxygen-consuming and hydrogen peroxide-generating oxidation of the a-carbon atom of L-Lys is KAC, which is described to further cyclize to 1,2-DP if the reaction is conducted in the presence of catalase (Kusakabe et al, 1980;Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LAAO is a flavoenzyme that requires flavin adenine dinucleotide (FAD) or a quinone as a cofactor [ 9 , 10 ]. This enzyme acts as an innate immune defence by catalysing the oxidative deamination of an L-amino acid substrate to produce an alpha-keto acid, ammonia and hydrogen peroxide [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of these two clusters suggested that the separation of the two subfamilies may have occurred when the two major clades of bacteria diverged, approximately three billion years ago [ 23 ]. Similarly, Campillo-Brocal et al [ 10 ] reported that the phylogenetic relationships of LAAO enzymes from animals were separated into vertebrate-related and gastropod-related groups. These findings suggest the possible separate evolution of LAAO enzymes in the innate immune systems of both animal groups [ 11 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar enzymes have since been described in a wide variety of organisms, from bacteria to vertebrates, with LAAO from snake venoms receiving particular attention [ 2 ]. Vertebrate, fungal, and gastropod LAAOs belong to distinct phylogenetic groups, whereas bacterial LAAOs do not constitute a discrete group, but present phylogenetic relationships to LAAOs of other species and d -amino acid oxidases (DAAOs) [ 3 ]. In contrast to snake venom LAAOs, mammalian LAAOs remain poorly explored.…”
Section: Introductionmentioning
confidence: 99%